2015
DOI: 10.4236/health.2015.77098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aldicarb Exposure on Cellular Immunity and Antioxidant Capacity in Kun-ming Mice

Abstract: Immune function and antioxidant defense play an important role in protecting animals against pathogens and in controlling oxidative stress, respectively. Aldicarb is of great concern for human health due to its toxic nature, its extensive usage and consequent pollution. The hypothesis that aldicarb exposure would suppress immune function and antioxidant capacity in Kunming mice was to be tested in the present study. Twenty-three adult male mice were randomly divided into the control (n = 11) and the aldicarb t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…ANOVA results showed that feed composition changes associated with pesticide and/or mineral fertilizer use (e.g., higher concentrations of aldicarb, diquat, and cadmium, but lower concentrations of fiber and antioxidants in feed crops) resulted in substantial differences in hormone profiles in rats. These findings are consistent with previous studies which reported endocrine and/or immune system disrupting effects of dietary exposure to pesticides and heavy metals such as Cd and Pb [ 21 , 32 , 33 , 34 , 37 , 40 , 41 , 67 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ], and additive or synergistic effects of combinations of endocrine-disrupting pesticides (insecticides, herbicide and/or fungicides) [ 21 , 33 , 81 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…ANOVA results showed that feed composition changes associated with pesticide and/or mineral fertilizer use (e.g., higher concentrations of aldicarb, diquat, and cadmium, but lower concentrations of fiber and antioxidants in feed crops) resulted in substantial differences in hormone profiles in rats. These findings are consistent with previous studies which reported endocrine and/or immune system disrupting effects of dietary exposure to pesticides and heavy metals such as Cd and Pb [ 21 , 32 , 33 , 34 , 37 , 40 , 41 , 67 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ], and additive or synergistic effects of combinations of endocrine-disrupting pesticides (insecticides, herbicide and/or fungicides) [ 21 , 33 , 81 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 93%
“…The unique factorial design of the dietary intervention study reported here allowed the effect of, and interactions between, different crop protection and fertilization regimes used in organic and conventional farming on crop composition and health-related physiological markers in rats to be identified. This study is also the first multigenerational study that compared the effect of feed composition differences resulting from organic and conventional crop protection and fertilization regimes on growth, hormone, and immune system parameters that were previously described as markers for the risk of overweight/obesity, metabolic syndrome and other chronic diseases in animals and humans [ 31 , 32 , 33 , 34 , 37 , 38 , 39 , 40 , 41 , 64 , 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation